Malnutrition and dietary pattern of children age below 12 years old living in Mukim Kemumin, Kota Bharu, Kelantan. - A.R., Nurul Hidayah; A.J., Rohana; Mohd Shariff, Zalilah; Sulaiman, Norhasmah; M., Kamarul Imran (Universiti Sains Malaysia, 2008)
A study to assess household food insecurity was carried out among 150 n=150) households in Mukim Kemumin, Kota Bharu, Kelantan. Apart from this study, an assessment of nutritional status and dietary pattern of children of the selected household aged below 12 years old was implemented, where a total of 150 households were selected through proportion sampling.